Untangling Heteroplasmy, Structure, and Evolution of an Atypical Mitochondrial Genome by PacBio Sequencing. Issue 1 (5th July 2017) - Peccoud, Jean; Chebbi, Mohamed Amine; Cormier, Alexandre; Moumen, Bouziane; Gilbert, Clément; Marcadé, Isabelle; Chandler, Christopher; Cordaux, Richard
Abstract: The highly compact mitochondrial (mt) genome of terrestrial isopods (Oniscidae) presents two unusual features. First, several loci can individually encode two tRNAs, thanks to single nucleotide polymorphisms at anticodon sites. Within-individual variation (heteroplasmy) at these loci is thought to have been maintained for millions of years because individuals that do not carry all tRNA genes die, resulting in strong balancing selection. Second, the oniscid mtDNA genome comes in two conformations: a ∼14 kb linear monomer and a ∼28 kb circular dimer comprising two monomer units fused in palindrome. We hypothesized that heteroplasmy actually results from two genome units of the same dimeric molecule carrying different tRNA genes at mirrored loci. This hypothesis, however, contradicts the earlier proposition that dimeric molecules result from the replication of linear monomers—a process that should yield totally identical genome units within a dimer. To solve this contradiction, we used the SMRT (PacBio) technology to sequence mirrored tRNA loci in single dimeric molecules. We show that dimers do present different tRNA genes at mirrored loci; thus covalent linkage, rather than balancing selection, maintains vital variation at anticodons. We also leveraged unique features of the SMRT technology to detect linear monomers closed by hairpins and carrying noncomplementary bases at anticodons. These molecules contain the necessary information to encode two tRNAs at the same locus, and suggest new mechanisms of transition between linear and circular mtDNA. Overall, our analyses clarify the evolution of an atypical mt genome where dimerization counterintuitively enabled further mtDNA compaction.